Production of candied jackfruit (Artocarpus heterophyllus) rags by combined osmotic and hot-air drying - Imbas, Donnalyn F. (2010)
Jackfruit (Artocarpus hetereophyllus var. Tinumbaga) rags have been regarded as fruit wastes in many jackfruit-producing countries, like the Philippines. In the study presented, focus was given on the efficient disposal of the fruit wastes. Hence, utilization of the jackfruit rags by its conversion into candied fruit by combined osmotic and hot-air drying was done. Osmotic dehydration was run using sucrose solution starting at 10degrees B sugar concentration and was increased, using the mean absorption rate of 1.80 degres B/hr, until the osmotic solution reached 60 degrees B. Hot-air drying was performed using a cabinet dryer maintained at a temperature of 60degreesC for 10 hours with constant hot air circulation. The resulting candied jackfruit rags had a moisture content of 40.55%. To keep the moisture content of the product at equilibrium, it should be stored in an environment with an equilibrium relative humidity of 77% or at 0.77 water activity. Moreover, the acceptability test conducted showed that the candied jackfruit rags were acceptable on the bases of the overall appearance, texture, flavor (sweetness), and after-taste liking. Polyethylene would be expected to keep the product in good condition at 25 degrees Celcius for up to a year.